Morphology of Colletotrichum Species Pathogenic to Pepper (Capsicum spp.) Fruits from Lampung - Yulianty, Yulianty; Ellyzarti, Ellyzarti; Lande, Martha L. (Proceeding International Conference on Global Resource Conservation, 2013)
Colletotrichum is knownÂ  causing anthracnose diseases on many plants. The taxonomy of Collettorichum spp. have been largely concerned with classical descriptive criteria such as conidial shape and size, and presence, absence and morphology of setae.The samples of Colletotrichum were collected from infected pepper fruits from the traditional market in Lampung. The samples observed under microscope and identification of Colletotrichum using standart texts. Two species were found; 1. Colletotrichum gloeosporioides (Penz.) Sacc. with four different conidial shapes,cylindrical with obtuse ends, cylindrical with a slightly tapered base and obtuse apex, slightly clavate, and cylindrical with obtuse ends with narrowing in the centre ; 2. Colletotrichum capsici (Syd.) Butler & Bisby with conidia falcate, fusiform, apices acute.Keyword : Anthracnose, Colletotrichum, Pepper